Progressive evolution of thyroid adenoma to thyroid carcinoma - Aisyah Elliyanti (Majalah Kedokteran Andalas, 2019)
Nodules (adenomas), enlarged thyroid (goiter) and inflammation of the thyroid (thyroiditis) are the most important risk factors for thyroid cancer. Adenomas have the largest increase in risk. Objectives: to discuss two cases of adenomas goiter that became aggressive during follow-ups. Cases: Two patients, with an average age of 64 years, referred to Nuclear Medicine dr. M. Djamil Hospital in Padang for bone scintigraphy examination. Both patients had thyroid surgery and histopathology results were adenomas. However, after the removal surgery, the patients did not have proper follow-ups. Both patients developed pelvic pain. Bone scintigraphy showed an increase of radiopharmaceutical uptake at pelvic bones and computerized tomography (CT Scan) result showed destruction at the pelvic bone areas. Conclusions: These cases highlight the necessity for adenoma thyroid patients with a risk factor for thyroid cancer to have a complete follow-up program and sufficient length period.